COOLTURA a special project on contemporary Philippine culture, the java programming language, the virtual reality modeling language, and the object-oriented paradigm - Bautista, Leah Rica A.; Lim, Jean Paulette C.; Pacaon, Alfredo Jr. C.; Sanchez, Cattleya J. (1996)
The Philippines is a fast-growing country on its way to Philippines 2000. There has been a lot of changes within the past few years In line with this is the growing interest of many people in this country Foreigners would want to know more about the country they might invest in and Filipinos abroad would want to know what is new in their motherland. There is now a need for a way to obtain fresh information about the modern day Philippine society. And what better place to get this information than the web.

A web-based, interactive, three-dimensional information system on contemporary Philippine culture is a most appealing way to retrieve such information. A web site where there are rooms for visitors to walk through Some objects in the rooms would be wrapped in images of paintings, photos, and text, clicking on these objects summons more information. Other objects would lead to games that the visitor can play with
Object-oriented technologies are now dictating what the World Wide Web will look like in the future. Though Hypertext Markup Language (HTML) pages still constitute the majority of web sites, two new languages emerged to change the way information is located and retrieved the Virtual Reality Modeling Language (VRML) and the Java Programming Language.

VRML is a scene description language. A viewer or browser parses a text file containing information on how this scene is displayed and displays it. The browser, however, does not just show what a three-dimensional world looks like, it also lets the visitor walk through it, turn right, turn left, and even click an object. The objective of VRML's creators is to provide web site visitors with a more natural, human-ese way of locating and retrieving information than just looking at two-dimensional pages and clicking away. There is a sense of 'there-ness' there.

JAVA, on the other hand, is a programming language. It is actually a dialect of the C++ programming language JAVA, however, provides for programming on the Internet, it allows programmers to create programs called applets that be run on any browser with Java support. These applets can be embedded into an HTML page. This supplies the interactivity and fun factor the World Wide Web needs.

By themselves, JAVA and VRML can be used to create more interesting web pages. However, these two technologies can be used to come up with an information system that is both perceptive and interactive. In the hope of harnessing the combined powers of these languages, the project-COOLTURA was created.
Note: FAQBook and proposal
Thesis (B.S. Computer Science)--University of the Philippines Diliman
Keywords: Java (Computer program language).; VRML (Computer program language).; Web sites